Nilai Pendidikan Akhlak Dalam Kitab Al-Barzanji Karya Syaikh Ja’far Al-Barzanji - Ali Ashadi (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this research is to find out the values ​​of moral education in the book of Al-Barzanji, and to find out the relevance of the values ​​of moral education in the book of Al-Barzanji related to the present context. While the writing of this research uses the type of library research (library research). And the method used in analyzing the data is content analysis with a descriptive approach. The data collection method used is the documentation method, using the primary book Maulid Al-Barzanji, by Abu Ahmad Najieh. While the secondary data are other books that are relevant to the title of this thesis. Based on this research, the researcher concludes that Shaykh Ja'far Al-Barzanji's thoughts about the value of education are based on the Qur'an and Hadith. The values ​​of moral education contained in the book of Al-Barzanji, by Shaykh Ja'far are still very relevant to the context of today's moral education. Noble values ​​include: honesty, simplicity, morals in association, birrul walidain (respect for both parents), morality to Allah SWT.